RUANG SENI DAN KULINER JALANAN DI SENEN - Andrean Hermanto; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2020)
As Urbanization blooms, related problems, especially those that affect community relations, become a 'hot topic' in developing projects based on 'Third Place'. The erosion of the community and its community often with the development of urbanization identified as Social Segregation becomes an interesting problem to be discussed by sociologists. The focus of the issue raised in this project is